Effectiveness of Leadership, Quality of School Management, and Performance of School Principal in Relation to The Teaching Quality of Teachers - Baharuddin, Baharuddin (LPPM Institut Pendidikan Nusantara Global, 2024)
The proficiency of teachers at SMAN 1 Bekasi in facilitating learning exchanges varies significantly. In fact, teachers frequently express dissatisfaction with the students they instruct, deeming them to be inadequately prepared. This study seeks to examine and assess the correlation between the efficacy of the Head of School's leadership, the school's management quality, and the Head of School's performance with the teaching quality of teachers at SMAN 1 Bekasi. This study used a mixed-methods methodology. Questionnaires, interviews, and observations serve as data collecting methods. The findings indicated that the leadership effectiveness of the head of school (X1), the quality of school administration (X2), and the leader's performance (X3) had a significant impact on the teaching quality of teachers (Y), both individually and collectively. The correlation between X1 and Y was 71.5%, the correlation between X2 and Y was 53.6%, and the correlation between X3 and Y was 35.7%. The combined correlation of the three independent variables (X1, X2, and X3) on the dependent variable (Y) was 72.4% and fell into the high category. Based on this study, it can be inferred that the quality of teaching in schools is significantly impacted by three primary characteristics: the leadership of the head of school, the quality of school management, and the performance of the head. Other variables also play a role in determining the overall quality. Every school principal has the ability to promote the enhancement of teaching by implementing efficient leadership, working towards achieving high-quality school administration, and enhancing performance to expedite school advancement.